2004
DOI: 10.1021/jp036842c
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase-Segregation and Transport in Nafion 117 from Molecular Dynamics Simulations:  Effect of Monomeric Sequence

Abstract: Nafion polyelectrolyte is widely used in polymer electrolyte membrane fuel cells (PEMFC) due to its high proton conductivity. The properties of hydrated Nafion are attributed to its nanophase-segregated structure in which hydrophilic clusters are embedded in a hydrophobic matrix. However, there has been little characterization of how the monomeric sequence of the Nafion chain affects the nanophase-segregation structure and transport in hydrated Nafion. To study such properties, we carried out molecular dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
551
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 455 publications
(608 citation statements)
references
References 87 publications
49
551
2
6
Order By: Relevance
“…In addition to the variation in density between the diblock and random copolymers, Jang et al 21 also observed a qualitative difference in the form of the nanophase-separated morphologies; namely that the sulfonate groups were more aggregated in the former case, and more uniformly distributed in the latter case. However, the pair correlation function of sulfur atoms in each case was similar, suggesting that it is the sulfonate groups on the same chain in the diblock polymer that aggregate, whereas in the random copolymer there are significant associations between sulfonate groups on different chains.…”
Section: Classical Molecular Mechanics Modelsmentioning
confidence: 99%
“…In addition to the variation in density between the diblock and random copolymers, Jang et al 21 also observed a qualitative difference in the form of the nanophase-separated morphologies; namely that the sulfonate groups were more aggregated in the former case, and more uniformly distributed in the latter case. However, the pair correlation function of sulfur atoms in each case was similar, suggesting that it is the sulfonate groups on the same chain in the diblock polymer that aggregate, whereas in the random copolymer there are significant associations between sulfonate groups on different chains.…”
Section: Classical Molecular Mechanics Modelsmentioning
confidence: 99%
“…62 These force fields were extensively tested and also successfully used in our previous studies. 63,64 For the surfactant, the benzene sulfonate part was described by the explicit all-atom model using the Dreiding force field, 65 and the alkyl tail part was described by the same united atom model used for decane. The total potential energy is given as follows:…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Classical molecular dynamics (MD) simulations have for instance been used to study the hydronium ions and water transport in the bulk membrane of PEMFCs [10][11][12][13][14][15][16]. These studies have provided important insight on the conduction mechanisms of proton through sulfonated acid groups via water clusters [10,11];o n the influence of membrane water content [10] and of morphology of nanophase in Nafion [13,14]; and on the effect of temperature [15,16]. Although atomistic models are widely used to investigate ion transport in bulk membrane, there have been relatively few studies of composite catalyst layer using this approach.…”
Section: Introductionmentioning
confidence: 99%